Motivasi dan Kepemimpinan terhadap Kepuasan Kerja Karyawan PT. Telelekomunikasi Indonesia (Persero) Tbk Pusat Makassar - Mappamiring, . (JURNAL ADMINISTRASI BISNIS (JAB), 2020)
This study aims to examine the influence of motivation and leadership on employee job satisfaction at PT. Telekomunikasi Indonesia (Persero) Tbk Pusat Makassar. Data collection using primary data obtained from questionnaires using simple random sampling technique. The population is all employees of PT. Telekomunikasi Indonesia (Persero) Tbk, Pusat Makassar with a total of 307 employees, while the sample taken is 75 respondents. it turns out that the research results show that the first hypothesis is rejected because it shows the results of the hypothesis test that there is no significant negative effect. It means that work motivation has no effect on employee job satisfaction. The second hypothesis is accepted because it shows a significant positive hypothesis test results. It means that leadership makes a real contribution to Employee Job Satisfaction. The third hypothesis is accepted because motivation and leadership simultaneously have a positive and significant effect on Employee Job Satisfaction.